Fé e interculturalidade : por uma teologia com rosto andino - CelIeri, Luis Paul Munoz (2022)
The present investigation, Faith and interculturality: for a theology with an Andean face, doctoral thesis in Systematic Theology, Line of research: Theology and contemporary thought, developed in the Postgraduate Program in Theology at PUCRS, has as main objective to discuss the elements of the Andean peoples in the light of faith and the development of their own theology which, as a consequence, will lead us to think of an intercultural theology. The methodology of this investigation is inspired by the so-called tripolar dialogue, a method that is supported by the following poles: culture; the Gospel revealed in Christ; and the Church's missionary experience in an Andean context. It is a decolonial, critical and propositional discussion for the renewal of theological thought and, consequently, of the way of being Christian.